Terrorism, the worker and the city : simulations and security in a time of terror - Howie, Luke (Gower, 2009)
Luke Howie's book considers what steps managers and employees can and should take to protect their businesses from the amorphous and indefinable threat of terrorism. Even where they don't perceive a high level threat, business managers who might face having to account for themselves to some post event Inquiry have taken action in consequence of the situation. Often, that action amounts to the introduction of what can be described as 'Simulated Security' which can be effective in terms of providing the reassurance to counter the terrorist objective of disrupting normal life through fear. With it.